Aspek Hukum Penyalahgunaan Fasilitas Negara Berupa Kendaraan Dinas di Lingkungan Pemerintahan Kabupaten Banyumas - Azyahiâ€™yah, Bian Arbi; Amarini, Indriati (UMPurwokerto Law Review, 2024)
Abstract Official vehicles are goods belonging to the Regional Government that are used to support official activities and functions in carrying out their duties according to their position. This study determines the formulation of the problem of legal aspects of abuse of state facilities in the form of official vehicles within the Banyumas Regency Government and constraints in controlling the abuse of state facilities in the form of official vehicles within the Banyumas Regency Government. This study aims to identify and analyze the legal aspects and constraints in controlling the misuse of official vehicles in the Government of Banyumas Regency. This research uses a normative juridical method which is a method carried out through library research in the form of research results, scientific journals and examines the main data, namely secondary data, namely Minister of Home Affairs Regulation Number 19 of 2016 concerning Guidelines for the Management of Regional Property. The results of the study show that the legal aspect of the misuse of official vehicles in Banyumas district has not taken firm action against officials or civil servants who have violated the use of official vehicles. Obstacles in controlling the misuse of official vehicles in Banyumas district is the lack of awareness of discipline, work ethic and understanding in the use of official vehicles and the lack of human resources in the BKAD Assets Sector which results in not being optimal in the supervision and management of Regional Property. Suggestions from the results of this study it is necessary to make a Regent Regulation or Regional Regulation concerning the use of official vehicles which regulate specifically and separately along with sanctions that will deter and the Government of Banyumas Regency needs to pay attention to and reinforce the ranks under them in carrying out their duties with full discipline and responsibility in using local property and increasing the number of human resources to optimize supervision and monitoring of BMD. Keywords: service vehicle, misuse, Banyumas regency Â  Abstrak Kendaraan dinas merupakan barang milik Pemerintah Daerah yang digunakan untuk menunjang kegiatan dinas dan fungsi dalam menjalankan tugas sesuai dengan jabatannya. Penelitian ini menetapkan rumusan masalah aspek hukum penyalahgunaan fasilitas negara berupa kendaraan dinas di lingkungan Pemerintahan Kabupaten Banyumas dan kendala dalam penertiban penyalahgunaan fasilitas negara berupa kendaraan dinas di lingkungan Pemerintahan Kabupaten Banyumas. Penelitian ini bertujuan mengetahui dan menganalisis aspek hukum dan kendala dalam penertiban penyalahgunaan kendaraan dinas di lingkungan Pemerintahan Kabupaten Banyumas. Penelitian ini menggunakan metode yuridis normatif yang merupakan metode dilakukan melalui studi pustaka (library research) berupa hasil penelitian, jurnal ilmiah dan menelaah data utama yakni data sekunder yaitu Peraturan Menteri Dalam Negeri Nomor 19 Tahun 2016 tentang Pedoman Pegelolaan Barang Milik Daerah. Hasil penelitian menunjukan bahwa aspek hukum dalam penyalahgunaan terhadap kendaraan dinas di kabupaten Banyumas belum adanya tindakan tegas untuk menindak oknum pejabat atau ASN yang melakukan pelanggaran terhadap penggunaan kendaraan dinas. Hambatan dalam penertiban penyalahgunaan kendaraan dinas di kabupaten banyumas kurangnya kesadaran disiplin, etos kerja dan pemahaman dalam penggunaan kendaraan dinas serta kurangnya SDM di BKAD Bidang Aset yang mengakibatkan tidak optimal dalam pengawasan dan pengelolaan Barang Milik Daerah. Saran dari hasil penelitian ini perlu dibuatkanya Peraturan Bupati atau Peraturan Daerah tentang penggunaan kendaraan dinas yang mengatur secara khusus dan tersendiri berserta sanksi yang akan membuat jera dan Pemerintah Kabupaten Banyumas perlu memperhatikan dan mempertegas jajaran yang ada dibawahnya dalam menjalankan tugas dengan penuh kedisiplinan dan tanggung jawab dalam menggunakan barang milik daerah serta meningkatkan jumlah SDM guna mengoptimalkan pengawasan dan pemantauan BMD. Kata kunci: kendaraan dinas, penyalahgunaan, kabupaten Banyumas